2013
DOI: 10.9787/pbb.2013.1.1.033
|View full text |Cite
|
Sign up to set email alerts
|

Development and Identification of Transgenic Rice Lines with Abiotic Stress Tolerance by using a Full-length Overexpressor Gene Hunting System

Abstract: This is an Open-Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/3.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. ABSTRACT The latest report on the draft genome of Brassica rapa sequence has been published. To elucidate the functions of these genes and to efficiently search for agriculturally useful genes, a Full-length c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…From the large FOX rice lines we developed and screened for abiotic stresses tolerance published earlier (Abdula et al 2013), BrCIPK1 was selected which showed tolerance to multiple abiotic stresses. The BrCIPK1 full-length complementary DNA (cDNA) was ligated into the pSB11 vector.…”
Section: Isolation Of Gene Vector Construction and Plant Transformamentioning
confidence: 99%
See 1 more Smart Citation
“…From the large FOX rice lines we developed and screened for abiotic stresses tolerance published earlier (Abdula et al 2013), BrCIPK1 was selected which showed tolerance to multiple abiotic stresses. The BrCIPK1 full-length complementary DNA (cDNA) was ligated into the pSB11 vector.…”
Section: Isolation Of Gene Vector Construction and Plant Transformamentioning
confidence: 99%
“…Indeed, in spite of having very similar amino sequences, these proteins respond differently to stress and regulate different signaling pathways (Pandey et al 2004). To facilitate the study of agronomically important genes, we developed 1500 FOX rice lines and evaluated them against abiotic stresses (Abdula et al 2013). Of these, BrCIPK1 plants showed consistently enhanced tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate overexpression, integration of the transgenes was constructed under the control of CaMV 35S and ubiquitin-1 promoter and NOS terminator (Abdula et al 2013). The whole construct was transformed into japonica rice cv.…”
Section: Development Of Brcp3-overexpressing Transgenic Ricementioning
confidence: 99%
“…Overexpression of this insert gene was constructed under the control of ubiquitin -1 promoter. The binary vector also carries hygromycin phosphotransferase (HPT) gene as a selectable marker (Abdula et al 2013). …”
Section: Vector Construction and Transformationmentioning
confidence: 99%
“…그 밖에 qLTG-3-1 (Fujino et al 2014 (Kump and Javomik 1996;Cho et al 1998). 추 출한 DNA는 λDNA (100 ng/ul)와 함께 1% agarose gel에서 확 인하였고 20 ng/ul로 정량하여 실험에 사용하였다 (Abdula et al 2013). 벼 유전자원의 resequencing은 HiSeq 2500 (Illumina) NGS (Next Generation DNA Sequencer)을 이용하여 short read sequence를 공주대학교 박용진 교수팀에서 생산하였다 .…”
unclassified